Are Chinese Teams Like Western Teams? Indigenous Management Theory to Leapfrog Essentialist Team Myths - Casas Klett, Tomas; Arnulf, Jan Ketil (Frontiers in Psychology, 2020)
Our study analyzes a gap in research on Chinese and Western management teams, based on a broad literature review. We claim that prevalent theoretical perspectives in the management team literature might be biased towards a Western-centric view of team dynamics. This obscures alternative ways of understanding top teams encompassing Chinese cultural traditions. We outline how an essentialist team conceptualization leads to a paradox consisting of three mutually contradicting myths. Myth 1 implies that Western groups of managers comply with theoretically “ideal” team processes and characteristics. Myth 2 derives from research literature on Chinese teams claiming that team features are assumed absent or weak in China due to cultural particularities. Paradoxically, the same research tradition constructs another third myth by reporting that Chinese teams successfully comply with the Western ideal team model. The three coexisting myths point to a theoretical confounding of contextual mediators in team processes. We discuss how indigenous Chinese leadership theory and Chinese systems of philosophy give Chinese teams access to distinct and effective team processes to reach high-performance outcomes. This paper aims to open the rich possibilities of Chinese management and team practices to the cross-cultural context, and on return to novel understanding of Western teams beyond traditional essentialist theory anchors.